2011
DOI: 10.1179/14653121141632
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wearing fixed orthodontic appliances on oral health-related quality of life among Brazilian children

Abstract: Children wearing a fixed orthodontic appliance had significantly worse OHRQoL compared with a control group with no malocclusion and not wearing a fixed appliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 18 publications
1
33
1
4
Order By: Relevance
“…The prevalence of school bullying among adolescents from different countries ranges from 5.4% to 67.5% [11,[13][14][15]. Cultural differences and different diagnostic methods related to school bullying in the population may explain this discrepancy.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The prevalence of school bullying among adolescents from different countries ranges from 5.4% to 67.5% [11,[13][14][15]. Cultural differences and different diagnostic methods related to school bullying in the population may explain this discrepancy.…”
Section: Introductionmentioning
confidence: 87%
“…Verbal school bullying episodes can be motivated by physical characteristics [5][6][7][8], such as obesity or excessive thinness [3,9]. Oral characteristics, including the position, color, and shape of teeth, can also affect self-image and quality of life [10,11]. Racial prejudice, religious, fashion clothing, height and hair type are some features that can also trigger verbal school bullying [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries is associated with psycho-emotional and/or systemic problems that (Kiyak, 2008;Costa, 2011).Malocclusion can lead to low self-esteem of individuals and can be one of the common symptoms of patients.…”
Section: Discussion:-mentioning
confidence: 99%
“…Some researchers have shown that orthodontic treatment using fixed appliances resulted in a significantly improved quality of life after two years of treatment [9,10]. On the other hand, other authors concluded that orthodontic treatment using fixed appliances significantly worsen the OHRQOL scores during treatment [11], and 24 hours following their insertion. A study that used the short form of the Child Perceptions Questionnaire (CPQ11-14) was used to compare difference in terms of impact on daily quality of life during the treatment period in two groups of children who received functional appliances and headgear respectively.…”
Section: Impact Of Orthodontic Treatment On Ohrqolmentioning
confidence: 99%